Evaluation of articular cartilage in knee osteoarthritis using hybrid multidimensional MRI. Issue 7 (July 2022) - Luo, P.; Hu, W.; Jiang, L.; Chang, S.; Wu, D.; Li, G.; Dai, Y.
Abstract : AIM: To evaluate a two-compartment model with a normal and an abnormal compartment using hybrid multidimensional (HM) magnetic resonance imaging (MRI) for detection of early stage degeneration in knee articular cartilage. MATERIALS AND METHODS: Forty mild osteoarthritis (OA; Kellgren–Lawrence grades [KLGs] 1 and 2), 27 moderate OA (KLG 3), and 23 healthy controls were included in the study. HM imaging using a two-compartment model was used to measure a normal and an abnormal cartilage compartment. The relationship between V normal and the degree of cartilage degeneration was examined using whole-organ MRI scores (WORMS). Receiver operating characteristic analysis was used to detect the ability of V normal, apparent diffusion coefficient (ADC), and T2 relaxation time to discriminate healthy controls from early OA. RESULTS: The intra- and interobserver reproducibility for calculated mean V normal values and WORMS indicated substantial agreement (intraclass correlation coefficient and weighted kappa >0.8). Overall, V normal in all compartments significantly differed among the healthy controls (50 ± 5.5%) and mild (41.1 ± 5.3%) and moderate OA (36.4 ± 8.1%). Mean V normal correlated negatively with the degree of OA progression ( ρ  = –0.778, p< 0.001). Mean V normal was characterised by a higher sensitivity (82.5%, 95% confidence interval [CI = 67.2–92.7) and specificity (87%, 95% CI = 66.4–97.2), with a cut-off value of 44.4%, compared to ADC and T2 values or a combination of ADC and T2 to differentiate early OA from healthy controls. CONCLUSIONS: HM-MRI coupled with values of ADC and T2 may provide value for detecting cartilage degeneration at an early stage of OA. Highlights: V normal based HM-MRI was associated with the degree of osteoarthritis progression. HM-MRI of articular cartilage makes it clinically feasible. HM-MRI provides additional information to detect early osteoarthritis.